Creating an Innovative Web-Backbone Participatory Radio-Based Agricultural Communication System: The Russian Rural Information Network - Ivan E. Perov (Journal of Applied Communications, 2002)
This project utilized a network of 300 agricultural specialists, a network of rural radio stations, and an Internet backbone agricultural information archive to develop an innovative new agricultural and rural development communication system for Russia. Experts were encouraged to share their research findings and field recommendations with the project, and in return they received a quarterly packet that included similar recommendations from the other experts. Rural radio stations were given raw scripts or taped program materials via CDs or Internet links for local broadcasting, and in return were asked to send the project copies of local scripts they developed and broadcast. The overall project was coordinated by Moscow State University, but also collaborated with and shared radio script information with the Press Video Center of the Ministry of Agriculture. By the project’s fifth year, the Internet site was receiving more than 1 million site visits per month. One innovative aspect of the project was a feedback form placed into each quarterly packet. Responses were received from 30 percent of recipients. Project staff found that recipients were willing to fill out very detailed feedback forms if they perceived that this would influence future materials they would receive.